ANIMALS AS CRIME VICTIMS - M. Pleshakov, Alexander; S. Shkabin, Gennadiy (Revista Gênero e Interdisciplinaridade, 2020)
Animals often become a subject of criminal attacks. However, their legal status is not well defined. The article is devoted to the analysis of the contradictions between the legal and biological characteristics of animals that have been subjected to criminal action. Today, in civil and criminal law they are considered as things, that is, inanimate objects. At the same time, numerous studies of the elementary behavior of representatives of the fauna show that, they can feel, experience emotions and possess rational abilities. In this regard, it becomes necessary to study further the legal status of animals, especially those who can carry out reasonable activities. The article provides various opinions of scientists on this issue. Attention is drawn to the position of authors who regard animals as a thing, animate objects. The authors’ position is expressed regarding proposals on the criminal legal protection of only vertebrates. The authors conclude that attacks on animals harm the moral principles of society. They propose to consider only mammals and birds as a subject of cruelty to animals.